Utilization of Soybean Milk Residue as Additive of Para Grass Silage - Srichana, Darunee; Suttitham, Wichai (Science & Technology Asia, 2015)
The objective of this study was to determine nutrients and ruminal digestibility of Para grass silage added with dried soybean milk residue (DSMR). The experimental design was completely randomized design with 4 treatments and 3 replications. The treatments were DSMR addition to Para grass at 0, 5, 10, and 15% fresh weight. The ensiling period was 30 days. The samples were collected and analyzed for nutrients and digestibility in rumen with batch culture for 24 h. The results showed that the increasing of DSMR (0, 5, 10 and 15) significantly increased dry matter (19.54, 23.23, 25.53 and 28.80%, respectively), crude protein (7.14, 13.71, 17.76 and 20.04 %DM, respectively), dry matter digestibility (32.54, 43.40, 55.53 and 63.52%, respectively), organic matter digestibility (30.12, 40.30, 53.44 and 61.81%, respectively) and crude protein digestibility (45.11, 73.79, 83.04 and 89.12%, respectively) of Para grass silages. Dry matter loss of the silages added with DSMR at 5-15% were not significantly different (8.18-11.78%) but significantly decreased when compared to the control (16.12%). Para grass silage added with 15% DSMR had higher organic matter content (P<0.05; 92.31 %DM) than the silage added with 0, 10 and 15% DSMR (90.16, 91.72 and 91.89%DM, respectively). In conclusion, Para grass silage added with 15% DSMR had the highest nutrients and ruminal digestibility. Keywords: Para grass silage; soybean milk residue; nutrient; digestibility; rumen; batch culture.